Method for measuring thorium and uranium content in geochemical samples

CN122962032APending Publication Date: 2026-10-23ZHENGZHOU MINERALS COMPOSITIVE UTILIZATION RES INST CHINESE GEOLOGICAL ACAD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610822859.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]鉴于背景技术的介绍,本发明提供了一种地球化学样品中钍铀含量的测量方法,用以解决现有的LA-ICP-MS测量地球化学样品中钍铀含量时由于样品基体效应和分馏效应导致测量结果不准确的问题

Benefits of technology

[0020]总而言之,本发明采用Li2B4O7和LiBO2混合熔剂先将地球化学标准物质和地球化学样品分别熔成玻璃片,通过经验系数X射线荧光光谱法测定样品玻璃片中的氧化铝,再利用LA-ICP-MS测定地球化学标准物质和地球化学样品玻璃片中27Al、232Th和238U的质谱强度,以27Al作为232Th和238U的内标,采用经验系数法拟合Th和U的校准曲线,从而准确测定了地球化学样品中的Th、U含量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962032A_ABST
    Figure CN122962032A_ABST
Patent Text Reader

Abstract

This invention relates to the field of radioactive element thorium and uranium testing technology, specifically to a method for measuring the thorium and uranium content in geochemical samples. First, geochemical standard materials and geochemical samples are separately fused into glass slides. The alumina content in the sample glass slides is determined by empirical coefficient X-ray fluorescence spectrometry. Then, LA-ICP-MS is used to determine the thorium and uranium content in the geochemical standard materials and geochemical sample glass slides. 27 Al、 232 Th and 238 The mass spectrum intensity of U, in 27 Al as 232 Th and 238 Using U as an internal standard, the calibration curves of Th and U were fitted using the empirical coefficient method, thereby accurately determining the Th and U contents in geochemical samples. The solid-solid analysis technique employed in this invention is simple to operate, highly efficient, and avoids the use of acid reagents. More importantly, it overcomes the shortcomings of sample effects and fractionation effects that lead to inaccurate measurement results, accurately measuring trace amounts of Th and U in geochemical samples.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radioactive element thorium and uranium testing technology, specifically to a method for measuring the thorium and uranium content in geochemical samples. Background Technology

[0002] Thorium (Th) and uranium (U) are important radioactive metallic elements with vast applications in industry and technology, widely used in nuclear power generation, medical and health applications, high-temperature industrial materials, and defense technology. Furthermore, the U-Th-Pb radioactive isotope system has extensive uses in geological dating. Accurate analysis of the U and Th content in geochemical samples is of great significance for strategic mineral exploration and Earth system science research. Geochemical samples generally include rocks, soils, and stream sediments. Currently, the main methods for analyzing Th and U in geochemical samples include spectrophotometry, atomic absorption spectrometry, X-ray fluorescence spectrometry, inductively coupled plasma atomic emission spectrometry (ICP-MS), and ICP-MS. Among these, ICP-MS has advantages such as low detection limits, wide linear range, few interferences, high precision, and fast analysis speed, and is therefore widely used in the analysis of Th and U.

[0003] Typically, ICP-MS analysis of Th and U requires dissolving the sample into a solution, which necessitates large amounts of acid, potentially polluting the environment and impacting the health of analysts. Current technology utilizes a mixed flux of Li₂B₄O₇ and LiBO₂ to fuse geochemical samples into glass slides at high temperatures. Trace amounts of these substances are then vaporized using laser ablation (LA) to form an aerosol. This aerosol is then carried by argon gas and ionized into ions at high temperatures, ultimately detected by mass spectrometry. This method is known as LA-ICP-MS. LA-ICP-MS employs a solid-solid analysis technique, avoiding the cumbersome process of preparing samples into solutions and eliminating the need for acid reagents, thus protecting the environment and the health of analysts.

[0004] However, while high-temperature melting with mixed flux can eliminate sample particle effects, mineral effects, and inhomogeneities, the content of Th and U in the glass slide remains unchanged due to sample matrix effects and the fractionation effect of LA-ICP-MS. 232 Th、 238 The intensity of U-mass spectrometry does not exhibit good linearity, leading to inaccurate measurement results.

[0005] Therefore, this application is submitted. Summary of the Invention

[0006] In view of the background art, the present invention provides a method for measuring the thorium and uranium content in geochemical samples, in order to solve the problem of inaccurate measurement results caused by sample matrix effect and fractionation effect when measuring the thorium and uranium content in geochemical samples using existing LA-ICP-MS.

[0007] likeFigure 2 As shown: When using the existing LA-ICP-MS method to test various geochemical standard materials (GBW07106, GBW07311, GBW07312, GBW07402, GBW07405, and GBW07408), the content of Th(U) is related to the content of the standard material glass slide. 232 Th ( 238 The average mass spectral intensity of Th and U is plotted as a scatter plot, showing that the content of Th and U in each geochemical standard material is related to the content of Th and U in the standard material glass slide. 232 Th、 238 The average mass spectrum intensity of U is not linear, which is due to sample matrix effects and elemental fractionation effects in LA-ICP-MS. Therefore, existing LA-ICP-MS methods can lead to inaccurate measurements of trace amounts of Th and U in geochemical samples.

[0008] To solve the above problems, the main technical solutions adopted by the present invention are as follows: A method for measuring the thorium-uranium content in a geochemical sample, comprising the following steps: S1. Using a mixed flux of Li2B4O7 and LiBO2, geochemical samples and several geochemical standard substances are first melted into sample glass slides and standard substance glass slides respectively, which greatly reduces the particle effect, mineral effect and inhomogeneity of the samples. Generally speaking, in order to establish a reliable linear relationship, cover the possible concentration range of the samples and ensure the repeatability and error of the method, there should be at least 3 types of geochemical standard substances. S2. The fluorescence intensity of Al-Kα in the sample glass slide was determined by XRF, and the content of Al2O3 in the sample glass slide was determined by the empirical coefficient method. Here, the empirical coefficient method is obtained by fitting the data of Al2O3 content and corresponding Al-Kα fluorescence intensity of each standard material glass slide. S3. LA-ICP-MS was used to measure the concentration of standard material glass slides and sample glass slides. 27 Al、 232 Th、 238 The mass spectrum intensity of U, and then 27 Al as 232 Th and 238 The internal standard of U is used, and the calibration curves of Th and U are fitted using the empirical coefficient method to accurately determine the content of Th and U in geochemical samples. The methods for plotting calibration curves and calculating the content of U and Th are the same. Taking Th as an example, when plotting the calibration curve, the content is calculated using... As the x-axis, with Using the vertical axis as the ordinate, the content calculation formula is: ; in: The mass fraction of Th in geochemical standard materials. The mass fraction of Th in the geochemical sample. This represents the mass percentage of Al2O3 in the geochemical sample. This represents the mass percentage of Al2O3 in geochemical standard materials. For the sample glass slide 232 The mass spectrum intensity of Th Standard material glass slide 232 The mass spectrum intensity of Th For the sample glass slide 27 Mass spectral intensity of Al In the standard material glass slide 27 Mass spectral intensity of Al.

[0009] because 27 Al and the element being analyzed 232 Th、 238 The response signal of U is similar to that of LA-ICP-MS (e.g. Figure 3 As shown: When using LA-ICP-MS to test the glass slide of the standard material prepared from geochemical standard material GBW07318, 27 Al、 232 Th、 238 U's signal response is almost identical), with 27 Al as 232 Th and 238 The internal standard of U can significantly improve the precision and accuracy of measurements. Therefore, this invention first uses XRF to determine the fluorescence intensity of Al-Kα in the sample glass slide, then uses the empirical coefficient method to determine the Al2O3 content in the sample glass slide, and finally uses LA-ICP-MS to determine the content of Al2O3 in the geochemical standard material and the actual sample glass slide. 27 Al、 232 Th and 238 The mass spectrum intensity of U, and with 27 Al as 232 Th and 238 Using U as an internal standard, and then fitting the calibration curves of Th and U using the empirical coefficient method, trace amounts of Th and U in actual geochemical samples were accurately determined.

[0010] Furthermore, in step S1, the geochemical reference materials include: GBW07106, GBW07311, GBW07312, GBW07402, GBW07405 and GBW07408.

[0011] In this technical solution, the above six geochemical standard materials are used to obtain calibration curves. These standard materials are similar to the geochemical samples in composition, structure and properties. The selection of six types can achieve the following beneficial effects: (1) a wider linear range, which can cover the complete range from trace to high concentration, avoiding extrapolation errors; (2) higher accuracy, multi-point fitting can reduce random errors and significantly improve the coefficient of determination R. 2 (3) It has higher reliability and can detect and correct matrix effects or nonlinear problems.

[0012] Furthermore, in step S2, the operating parameters for XRF determination of Al-Kα fluorescence intensity are as follows: a voltage of 50kV and a current of 60mA are used, pentaerythritol crystal (PET) is used as the spectroscopic crystal, and the 2θ angles of the peak, background 1, and background 2 are 144.748°, 143.400°, and 146.750° respectively, the counting times of the peak, background 1, and background 2 are 40s, 10s, and 10s respectively, the detector is a gas flow counter, and the pulse amplitude analysis range is 130-290.

[0013] In this technical solution, a voltage of 50kV and a current of 60mA are used for XRF measurement, along with a PET crystal and a gas flow counter. Under the above measurement parameters, the Al signal can be maximized and the background noise can be reduced, ensuring the accuracy and sensitivity of the Al measurement results.

[0014] Furthermore, in step S3, the operating parameters of LA are: energy density 9 J / cm³. 2 The pulse frequency was 11 Hz, the beam size was 100 μm, and the flow rate of the carrier gas He was 400 mL / min.

[0015] In this technical solution: energy density 9J / cm³ 2 This design ensures effective ablation of the glass substrate, preventing Th and U signals from falling below the detection limit, while also suppressing thermal fractionation effects to some extent. A pulse frequency of 11 Hz, matched with a 40 ms dwell time, ensures complete acquisition of the aerosol generated by each laser pulse. A beam size of 100 μm guarantees sample representativeness. A He carrier gas flow rate of 400 mL / min ensures aerosol transmission efficiency exceeding 90% and stabilizes the delay time within ±0.5 s. These parameters, constrained within the aforementioned ranges, interact and synergistically contribute to balancing the sensitivity, accuracy, and spatial resolution of Th and U measurements.

[0016] Furthermore, in step S3, the dwell time during LA-ICP-MS measurement is 40ms.

[0017] In LA-ICP-MS analysis using a quadrupole mass analyzer, the dwell time is the duration for which the quadrupole remains at a specific mass-to-charge ratio (m / z) to acquire signals. The length of the dwell time directly affects the data quality and the accuracy of the analysis. Through repeated experiments, the applicant discovered that when the dwell time is set to 40ms during the test in step S3 of this invention, a good balance between signal-to-noise ratio and analysis efficiency can be achieved, resulting in high signal stability, fast analysis speed, and high resolution.

[0018] Furthermore, in step S1, the mass ratio of Li2B4O7 to LiBO2 in the mixed flux is 2:1. Specifically, the mixed solvent is mixed with the geochemical standard material and the geochemical sample at a mass ratio of 1:0.1 and stirred evenly. The mixture is then placed in a platinum crucible, ammonium bromide solution is added dropwise, and the temperature is raised to 1100℃ and melted into a glass sheet.

[0019] Furthermore, in step S1, after heating to 1100℃, the temperature is maintained for at least 12 minutes. During this period, the mixed flux and the geochemical sample or geochemical standard material undergo pre-melting, melting, and settling steps in sequence. Afterward, the crucible is removed and rotated 360° horizontally 10 times, and then naturally cooled to room temperature.

[0020] In summary, this invention uses a mixed flux of Li₂B₄O₇ and LiBO₂ to first melt geochemical standard materials and geochemical samples into glass slides. The alumina content in the sample glass slides is determined by empirical coefficient X-ray fluorescence spectrometry, and then LA-ICP-MS is used to determine the alumina content in the geochemical standard materials and geochemical sample glass slides. 27 Al、 232 Th and 238 The mass spectrum intensity of U, in 27 Al as 232 Th and 238 Using U as an internal standard, the calibration curves of Th and U were fitted using the empirical coefficient method, thereby accurately determining the Th and U contents in geochemical samples.

[0021] Compared with existing technologies, the measurement method proposed in this invention adopts solid-solid analysis technology, which simplifies the analysis operation, improves the analysis efficiency, avoids the use of acid reagents, protects the environment and the health of analysts, and, more importantly, overcomes the defects of inaccurate measurement results caused by sample effect and fractionation effect, accurately measuring trace Th and U in geochemical samples. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 The calibration curves for Th and U in the geochemical standard material in Example 1 are shown.

[0024] Figure 2 When determining the content of Th(U) in geochemical standard materials using the existing LA-ICP-MS method, the relationship between the content of Th(U) in the standard material glass slide and the content of Th(U) in the standard material is as follows: 232 Th ( 238 Scatter plot of average mass spectrum intensity of U).

[0025] Figure 3 For LA-ICP-MS testing of standard glass slides (GBW07318) 27 Al、 232 Th and 238 U signal diagram.

[0026] Figure 4 This is a calibration curve of Al2O3 determined by XRF analysis of the Al2O3 content in the glass slides of various standard materials in Example 1. Detailed Implementation

[0027] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0028] All chemical raw materials used in the following examples and comparative examples were commercially available, and the performance testing methods and operations involved were conventional testing methods and operations in the art. The experimental apparatus involved specifically included: a fully automated sample melting machine (TNRY-01A, Luoyang Tena Experimental Equipment Co., Ltd.), a laser ablation system (RESOLUTION SE, Applied Spectra, USA), an X-ray fluorescence spectrometer (ZSX Primus II, Rigaku Corporation, Japan), and an inductively coupled plasma mass spectrometer (iCAP Qc, ThermoFisher, USA).

[0029] Example 1 S1. Using a mixed flux of Li2B4O7 and LiBO2 at a mass ratio of 2:1, geochemical samples (simulated by geochemical standard material GBW07103), geochemical standard materials GBW07106, GBW07311, GBW07312, GBW07402, GBW07405, and GBW07408 were melted into sample glass slides and 6 standard material glass slides, respectively. When preparing each glass slide, the mass of the mixed solvent was 7g, and the mass of the geochemical sample or geochemical standard material was 0.7g. After mixing the raw materials with a small glass rod, the mixture was poured into a platinum-gold crucible (the mass ratio of platinum to gold was 95:5), and two drops of 300g / L ammonium bromide solution were added with a dropper. The crucible was then placed in a melting machine heated to 1100℃ and held for 885s. After that, the crucible was removed and rotated 360° horizontally 10 times. After being placed and cooled to room temperature, the resulting glass slides were removed. S2. The fluorescence intensity of Al-Kα in the sample glass slide was determined by XRF, and the content of Al2O3 in the sample glass slide was determined by empirical coefficient method. The specific working parameters were as follows: 50kV voltage and 60mA current were used, pentaerythritol crystal was used as the spectroscopic crystal, and the 2θ angles of the peak, background 1 and background 2 were 144.748°, 143.400° and 146.750° respectively. The counting times of the peak, background 1 and background 2 were 40s, 10s and 10s respectively. The detector was a gas flow counter, and the pulse amplitude analysis range was 130-290°. Specifically, the fluorescence intensity of Al-Kα in six standard glass slides was first measured using XRF, and then plotted as follows: Figure 4 The Al2O3 calibration curve is shown. Then, based on the empirical coefficients of the Al2O3 calibration curve, the content of Al2O3 in the sample glass slide is determined according to the measured fluorescence intensity of Al-Kα in the sample glass slide. S3. LA-ICP-MS was used to measure the concentration of standard material glass slides and sample glass slides. 27 Al、 232 Th、 238 The mass spectrometry intensity of U (randomly measured at 4 points; LA operating parameters: energy density 9 J / cm²) 2 The pulse frequency was 11 Hz, the beam size was 100 μm, and the flow rate of the carrier gas He was 400 mL / min; the residence time during LA-ICP-MS measurement was 40 ms. 27 Al as 232 Th and 238 The internal standard of U was used to fit the calibration curves of Th and U using the empirical coefficient method, and the contents of Th and U were calculated. Specifically, when fitting the calibration curve of Th, LA-ICP-MS test data of various standard material glass slides were used as fitting data, resulting in the following: Figure 1 (A) shows the calibration curve of Th in geochemical standard materials. The horizontal and vertical axes satisfy y = 0.001700x + 0.0001423 and the coefficient of determination R 2 =0.9990, combined with the LA-ICP-MS test data of the sample glass slide, according to the formula: Calculate the mass percentage of Th in the geochemical sample, where: The mass fraction of Th in geochemical standard materials. The mass fraction of Th in the geochemical sample. This represents the mass percentage of Al2O3 in the geochemical sample. This represents the mass percentage of Al2O3 in geochemical standard materials. For the sample glass slide 232 The mass spectrum intensity of Th Standard material glass slide 232 The mass spectrum intensity of Th For the sample glass slide 27 Mass spectral intensity of Al In the standard material glass slide 27 The mass spectrometry intensity of Al was used to calculate the Th content as 51 μg / g. Obtain the calibration curve for U using a similar procedure as above, such as... Figure 1 (B) shows the calibration curve of U in geochemical standard materials, with the x and y axes satisfying y = 0.001800x + 0.0005437 and the coefficient of determination R. 2 =0.9993, substituting into the formula, the content of U is found to be 20.1 μg / g.

[0030] Example 2 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07104", and everything else remained the same as in Example 1.

[0031] Example 3 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07105", and everything else remained the same as in Example 1.

[0032] Example 4 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07107", and everything else remained the same as in Example 1.

[0033] Example 5 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07306", and everything else remained the same as in Example 1.

[0034] Example 6 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07308", and everything else remained the same as in Example 1.

[0035] Example 7 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07310", and everything else remained the same as in Example 1.

[0036] Example 8 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07318", and everything else remained the same as in Example 1.

[0037] Example 9 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07403", and everything else remained the same as in Example 1.

[0038] Example 10 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07404", and everything else remained the same as in Example 1.

[0039] Example 11 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07406", and everything else remained the same as in Example 1.

[0040] Example 12 Compared with Example 1, the test sample was changed from "GBW07103" to "GBW07407", and everything else remained the same as in Example 1.

[0041] Comparative Example 1 Compared with Example 1, not based on 27 Al was used as an internal standard. The calibration curves of Th and U were not fitted using the empirical coefficient method. Instead, the contents of Th and U in GBW07103 were tested solely by LA-ICP-MS.

[0042] Comparative Example 2 Compared with Example 2, not based on 27 Al was used as an internal standard. The calibration curves of Th and U were not fitted using the empirical coefficient method. Instead, the contents of Th and U in GBW07103 were tested solely by LA-ICP-MS.

[0043] The measurement results of each embodiment and comparative example are shown in Table 1.

[0044] Table 1. Measurement results of Th and U in each example and comparative example (μg / g)

[0045] As shown in Table 1, the test results of Examples 1-12 show that when 12 geochemical standard materials were used as test samples and the measurement method proposed in this invention was applied, the measured values ​​were consistent with the certified values. A comparison of the test results of Example 1 and Comparative Example 1, and of Example 2 and Comparative Example 2, shows that the LA-ICP-MS measurement... 27 Al、 232 Th、 238 The signal response of U is almost identical, and the present invention uses 27 Al as 232 Th and 238 The internal standard U can effectively reduce the sample matrix effect and the fractionation effect of LA-ICP-MS, thereby significantly improving the precision and accuracy of the measurement.

[0046] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make modifications, alterations, substitutions, and variations to the above embodiments within the scope of the present invention. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of the different embodiments or examples.

Claims

1. A method for measuring the thorium-uranium content in a geochemical sample, characterized in that: The following steps are included: S1. Using a mixed flux of Li2B4O7 and LiBO2, geochemical samples and several geochemical standard substances are first melted into sample glass slides and standard substance glass slides, respectively. S2. The fluorescence intensity of Al-Kα in the sample glass slide was determined by XRF, and the content of Al2O3 in the sample glass slide was determined by empirical coefficient method. S3. LA-ICP-MS was used to measure the concentration of standard material glass slides and sample glass slides. 27 Al、 232 Th、 238 The mass spectrum intensity of U, and then... 27 Al as 232 Th and 238 The internal standard of U is used, and the calibration curves of Th and U are fitted using the empirical coefficient method to accurately determine the content of Th and U in geochemical samples. The methods for plotting calibration curves and calculating the content of U and Th are the same. Taking Th as an example, when plotting the calibration curve, the content is calculated using... As the x-axis, with Using the vertical axis as the ordinate, the content calculation formula is: ; in: The mass fraction of Th in geochemical standard materials. The mass fraction of Th in the geochemical sample. This represents the mass percentage of Al2O3 in the geochemical sample. This represents the mass percentage of Al2O3 in geochemical standard materials. For the sample glass slide 232 The mass spectrum intensity of Th Standard material glass slide 232 The mass spectrum intensity of Th For the sample glass slide 27 Mass spectral intensity of Al In the standard material glass slide 27 Mass spectral intensity of Al.

2. The method for measuring the thorium-uranium content in a geochemical sample according to claim 1, characterized in that: In step S1, the geochemical reference materials include: GBW07106, GBW07311, GBW07312, GBW07402, GBW07405 and GBW07408.

3. The method for measuring the thorium-uranium content in a geochemical sample according to claim 1, characterized in that: In step S2, the XRF parameters for measuring the fluorescence intensity of Al-Kα are as follows: a voltage of 50 kV and a current of 60 mA are used, pentaerythritol crystal is used as the spectroscopic crystal, and the 2θ angles of the peak, background 1, and background 2 are 144.748°, 143.400°, and 146.750° respectively. The counting times of the peak, background 1, and background 2 are 40 s, 10 s, and 10 s respectively. The detector is a gas flow counter, and the pulse amplitude analysis range is 130-290°.

4. The method for measuring the thorium-uranium content in a geochemical sample according to claim 1, characterized in that: In step S3, the operating parameters of the LA are: energy density 9 J / cm³. 2 The pulse frequency was 11 Hz, the beam size was 100 μm, and the flow rate of the carrier gas He was 400 mL / min.

5. The method for measuring the thorium-uranium content in a geochemical sample according to claim 1, characterized in that: In step S3, the dwell time during LA-ICP-MS measurement is 40 ms.

6. The method for measuring the thorium-uranium content in a geochemical sample according to any one of claims 1-5, characterized in that: In step S1, the mass ratio of Li2B4O7 to LiBO2 in the mixed flux is 2:

1. The specific operation is as follows: the mixed solvent is mixed with the geochemical standard material and the geochemical sample at a mass ratio of 1:0.1 and stirred evenly, and placed in a platinum crucible. Ammonium bromide solution is added dropwise, and then the temperature is raised to 1100℃ and melted into a glass sheet.

7. The method for measuring the thorium-uranium content in a geochemical sample according to claim 6, characterized in that: In step S1, the temperature is raised to 1100°C and held for at least 12 minutes. After that, the crucible is removed and rotated 360° horizontally 10 times, and then allowed to cool naturally to room temperature.